REFORMULATION OF THE PENAL MEDIATION ARRANGEMENT IN TRAFFIC OFFENSES - Yudhi Darmansyah; Faizin Sulistio; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
The implementation of penal mediation within the Indonesian legal system presents a promising alternative to traditional criminal proceedings, especially in cases involving traffic accidents caused by negligence. Penal mediation offers a non-litigation mechanism that prioritizes rehabilitation, the restoration of relationships between victims and offenders, and the promotion of peace. While traffic accidents cause significant harm to victims, involving them in the mediation process helps clarify the offender's responsibilities and provides an opportunity for restorative justice. Moreover, penal mediation can help prevent the negative consequences of imprisonment, which not only affects the offender but also their family and society at large. However, the absence of specific legislation governing penal mediation within the Criminal Justice System poses challenges, making it difficult for law enforcement officials to provide legal certainty in cases involving traffic violations under the Traffic Law. Therefore, it is essential for future reforms to address these gaps, ensuring that penal mediation can be effectively implemented in traffic accident cases to achieve more humane and restorative outcomes.